Melatonin, insomnia and the use of melatonergic drugs - Srinivasan, Venkatramanujam; Zakaria, Rahimah; Othman, Zahiruddin; Brzezinski, Amnon (Informatics Publishing Ltd. and Society for Reproductive Biology and Comparative Endocrinology, 2012)
Due to inconsistency among reports on the therapeutic efficacy of melatonin, attention has been focused on the development of more potent melatonin analogues with prolonged effects. Melatonergic drugs, ramelteon and agomelatine have been effective in treating either sleep disorders or sleep disturbances associated with depressive disorders. MT1 and MT2 melatonergic receptor agonist, ramelteon, was found effective in increasing total sleep time and sleep efficiency, and in reducing sleep latency in patients with insomnia. No reduction in its efficacy was found even after 6-12 months of continuous use. The mechanism of sleep promoting action of ramelteon is entirely different from that of conventional hypnotics that are in use today. Ramelteon’s use is not associated with any adverse effects even after six months to one year after its continuous usage. Another melatonergic drug, agomelatine, has also been found effective in improving sleep efficiency and quality, and this action of agomelatine is suggested to be one of the major mechanism by which agomelatine ameliorates depressive symptoms in patients with major depressive disorders and bipolar disorders.